Development of a STEM-Based Teaching Module Integrated with Indigenous Knowledge of the Sade Traditional House to Improve Students’ Geometry Problem-Solving Skills - Rasyidin Rasyidin; I Ketut Sukarma; Akhmad Sukri; Sutarto Sutarto (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aims to develop a Science, Technology, Engineering, and Mathematics (STEM)-based teaching module that integrates the Indigenous Knowledge of the Sade Traditional House into geometry curriculum and to test its validity, practicality, and effectiveness in improving students’ problem-solving skills. This study employed the Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 69 students: 34 in the experimental class and 35 in the control class. The research instruments included an expert validation sheet, a student response questionnaire, and problem-solving ability tests in the form of pretests and posttests. The expert validation results showed a percentage of 88%, categorized as highly valid, while student responses yielded a percentage of 86.18%, categorized as highly practical. An analysis of learning outcomes showed that the average pretest score for the experimental class increased from 33.76 to 74.85 on the posttest, while the control class’s score increased from 36.89 to 41.63. The results of the independent samples t-test showed a significant difference between the two classes on the posttest (p < 0.001), proving that the developed teaching module was effective in improving students’ problem-solving skills. The integration of Indigenous Knowledge of the Sade Traditional House into geometry instruction created a contextual and meaningful learning experience and strengthened the connection between mathematical concepts and local culture.